AKULTURASI BUDAYA DALAM UPACARA KEMATIAN MASYARAKAT KOTA SANTRI KEDIRI LOMBOK BARAT - Lalu Ahmad Busyairy (Harmoni, 2018)
This paper is aimed at understanding forms of funeral rituals and cultural acculturation in the procession of funeral rituals in the society of the Santri City Kediri, West Lombok. This research applies qualitative approach that has starting point from an assumption that not all that appears is real. The data collection is conducted through observation, interview, and documentation. The research discovers that, first, the customary funeral ritual is the customary ritual that has been existing since long ago before the coming of Islam, that is still conducted by the people of the Santri City Kediri, West Lombok up to this day. Second, within the process of the funeral ritual, there are several series of rituals that must be conducted as they are related each other. The process begins from preliminary steps, bathing, shrouding, burying, and commemorating the death day. Third, in the funeral ritual, the influence of custom has been existing in the role and the cultural acculturation during the performance, starting from the disintermenting to the religious-chanting (dhikr) in the third to the ninth day, even to the hundredth or thousandth day (nyeribu).